Symposium 3: The 7Cs of Learning Design – a new approach to rethinking design practice - Conole, Gráinne (Proceedings of the International Conference on Networked Learning, 2014)
Designing for learning is arguably the key challenge facing education today; new technologies offer a plethora of ways in which learners can interact with rich multimedia, communicate and collaborate. Despite this teachers lack the necessary digital literacy skills to make effective design decisions that are pedagogically informed and make appropriate use of technologies. Learning Design has emerged in the last ten years as a means of addressing this, by providing teachers with guidance and support for their design practices. Learning Design is predicated on three aspects: guidance, visualisation and sharing. The paper will describe the development and evaluation of a new framework for Learning Design, the 7Cs of Learning Design. The framework consists of the following elements: Conceptualise (i.e. what are you designing and why, who are you designing for?), Capture (in terms of capturing resources to be used and activities around Learner Generated Content), Communicate (mechanisms to foster communication), Collaborate (mechanisms to foster collaboration), Consider (activities to promote reflection and enable assessment), Combine (combining the activities to give a holistic overview of the design and associated learning pathways), and Consolidate (in terms of running the design in a real learning context, evaluating, refining and sharing the design). The paper will describe the framework and how it can be used, along with an evaluation of its application in practice. It will conclude by contextualising this work within recent broader developments in the field. The framework can be used by individual teacher or with groups of teachers co-designing learning interventions. The latter has been effectively delivered in a series of workshops we have run over the past year.